Land Lapse Phenomenon and Surface Subsidence Law of Shield Tunnel Passing Through Rock-Bearing Formation - Guangming, Yu; Pengju, Xia; Yongyi, Zhang; Qimeng, Shi; Jun, Lei; Pengfei, Song; Zhiwen, Tan; Hao, Liu; Ze, Chen (Frontiers in Earth Science, 2022)
When constructing subway tunnels in coastal cities, boulders with high strength and large volume are often encountered. A large number of engineering practices have shown that the existence of boulders will destroy the unity and homogeneity of the stratum. If the tunnel is not properly handled during crossing construction, it will lead to the collapse of surrounding rock; in serious cases, it may induce ground collapse, damage the surrounding buildings, and endanger the safety of people’s lives and property. Firstly, with the help of similar material simulation test, this paper reproduces the phenomenon of vault collapse and surface collapse when the tunnel passes through the boulder stratum, explores the law of stratum collapse and surface settlement caused by the boulder in the process of tunnel excavation, and puts forward the “weightlessness weak surface effect” of the boulder stratum disturbed. Then, taking the Liu-Bai inter-district tunnel project of Shenzhen Metro Line 13 as an example, Midas GTS NX numerical simulation software is used to compare and analyze the influence characteristics of surrounding rock deformation and surface settlement caused by the presence or absence of boulders in the tunnel through the stratum and verify the “weightlessness weak surface effect” of the boulder stratum disturbed. Finally, the engineering treatment measures for the Liu-Bai inter-district tunnel project of Shenzhen Metro Line 13 crossing the boulder stratum are given. The research results are of great significance to guide the prediction and treatment of collapse and surface settlement when crossing the boulder stratum in the tunnel construction project.